BUSINESS MODELS FOR ONLINE EDUCATION - Lorenzo, George (Online Learning, 2006)
Nine institutions—Colorado State University, Dallas County Community College District (DCCCD), Duquesne University, Georgia Institute of Technology, University of Central Florida, The University of Illinois at Springfield, University of Massachusetts Lowell, University of Michigan, University of Georgia—share information about their business models.